(untitled) (Global Journal of Science Frontier Research, 2017)
In this work, the adsorption efficiency of fishscales was investigated as an environmentally-friendly and cheap alternative sorbent for removing excess nitrate and nitrite from wastewater. The pulverized size of the fishscales was found to be ≤60 µm, with rough surfaces. Multivariate methodology was employed for optimization of parameters that affect sorption; initial ion concentration which were found to be 28.44 mg/L (NO 2 - ) and 28.29 mg/L (NO 3 - ), the sorbents; 78.48 mg/L (NO 2 - ) and 71.17 mg/L (NO 3 - ), contact time, which were found to be 65.72 min (NO 2 - ) and 74.84 min (NO 3 - ), and solution pH 7.97 (NO 2 - ) and 7.00 (NO 3 - ). The optimized adsorption method exhibited high percentage removal efficiencies toward nitrite and nitrate removal from real wastewater samples at 91.42% and 74.60% with a relative standard deviation (RSD) of 1.44% and 2.09% for n = 3 respectively. Physico-chemical characterization of the fishscales showed multiple functional groups including, carboxylic, hydroxyl and carbonyls. The adsorption of ions onto valuarized fishscales was endothermic and spontaneous and the adsorption data followed second-order kinetics.